2012
DOI: 10.1002/ajmg.a.35539
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐economic factors affect mortality in 47,XYY syndrome—A comparison with the background population and Klinefelter syndrome

Abstract: Mortality among males with 47,XYY is increased due to a host of conditions and diseases. Clinical studies have suggested a poorer educational level and social adaptation among 47,XYY persons. We wanted to study the socio-economic profile in 47,XYY persons and the impact on mortality. We conducted a register study using several Danish nationwide registries. 206 47,XYY men and 20,078 controls from the background population and 1,049 controls with Klinefelter syndrome were included. Information concerning marital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 38 publications
1
12
0
3
Order By: Relevance
“…Late diagnosis as well as non-diagnosis of SCAs have been a continuous concern [2527, 38] since SCAs are associated with increased morbidity and mortality [3, 5, 20, 23, 39], learning and/or behavioral disabilities [4045] as well as reduced socioeconomic outcomes. Although there is lack of evidence regarding the influence of age at diagnosis on long-term outcomes, we believe that early diagnosis will provide better overall long-term outcome in SCAs by providing an opportunity for timely intervention against associated health problems as well as against learning and behavioral problems.…”
Section: Discussionmentioning
confidence: 99%
“…Late diagnosis as well as non-diagnosis of SCAs have been a continuous concern [2527, 38] since SCAs are associated with increased morbidity and mortality [3, 5, 20, 23, 39], learning and/or behavioral disabilities [4045] as well as reduced socioeconomic outcomes. Although there is lack of evidence regarding the influence of age at diagnosis on long-term outcomes, we believe that early diagnosis will provide better overall long-term outcome in SCAs by providing an opportunity for timely intervention against associated health problems as well as against learning and behavioral problems.…”
Section: Discussionmentioning
confidence: 99%
“…47,XYY syndrome is also a relatively common genetic condition, occurring in males in ~1 per 1000 live births [ 5 ]. Many are diagnosed in adolescence or adulthood, as many who have this condition present only with tall stature.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it is believed that 85% or more of males with XYY are never diagnosed [ 2 ]. Tall stature in 47,XYY syndrome is thought to be due to triplicate expression of the short stature homeobox-containing gene ( SHOX ) located on the distal ends of Xp and Yp [ 5 ]. Other characteristics include autistic traits and neurocognitive changes, such as speech and language problems, and reduced motor skills and educational achievement [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, WM, GMV, SA and CT abnormalities observed in the posterior parietal cortex could negatively impact attention, sensorimotor processing and integration of visual and auditory constructs (Arnsten & Rubia ; Cohen et al ; Iacoboni ). Taken together, it is possible that the cognitive profile resulting from these brain alterations could contribute to the increased risk for a diagnosis of ASD (Ross et al ) and the relatively decreased socioeconomic outcome (Stochholm et al ) reported in the XYY population.…”
Section: Discussionmentioning
confidence: 99%